The reality of the development of the Faculty of Arts between institutional accreditation and total quality from the point of view of the heads of departments at Sebha University, Faculty of Arts (Journal of Human Sciences, 2021)
The research aimed to identify the role of developing the Faculty of Arts between institutional accreditation and total quality from the point of view of the heads of departments at the Faculty of Arts, Sebha University, and to shed light on institutional accreditation, total quality and development and improvement processes within the Faculty of Arts. The researcher used the descriptive analytical approach to know the views of department heads. Faculty of Arts in the reality of development between institutional accreditation and total quality, and the research sample consisted of (12) heads of department at the Faculty of Arts, and the research tool included a questionnaire prepared by the researcher, The results of the research concluded: There is a range of the reality of development in the Faculty of Arts between accreditation, institutional and total quality from the point of view of department heads at Sebha University, followed by no statistically significant differences over the extent of the reality of the development of the Faculty of Arts between institutional accreditation and total quality due to the gender variable (males and females), Academic qualifications (Master's and Ph.D.), and years of experience from 4 years to 12 years or more.